2016
DOI: 10.1016/j.nbd.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

The polarity protein Par3 regulates APP trafficking and processing through the endocytic adaptor protein Numb

Abstract: The processing of amyloid precursor protein (APP) into β-amyloid peptide (Aβ) is a key step in the pathogenesis of Alzheimer’s disease (AD), and trafficking dysregulations of APP and its secretases contribute significantly to altered APP processing. Here we show that the cell polarity protein Par3 plays an important role in APP processing and trafficking. We found that the expression of full length Par3 is significantly decreased in AD patients. Overexpression of Par3 promotes non-amyloidogenic APP processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 60 publications
2
38
0
Order By: Relevance
“…Our recent studies found that there is a significant decrease in Par3 protein levels in the temporal cortex of AD patients (Sun et al, 2016). If abnormalities in Par3/aPKC regulated Ser498 phosphorylation are important for AD progression, one would predict to see a decrease in Ser498 phosphorylation in AD patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent studies found that there is a significant decrease in Par3 protein levels in the temporal cortex of AD patients (Sun et al, 2016). If abnormalities in Par3/aPKC regulated Ser498 phosphorylation are important for AD progression, one would predict to see a decrease in Ser498 phosphorylation in AD patients.…”
Section: Resultsmentioning
confidence: 99%
“…We found that Par3 regulates APP trafficking and intracellular Aβ generation in neurons (Sun et al, 2016). Here we found Par3 is also involved in the trafficking of BACE1; however, Par3 showed distinct effects on APP and BACE1.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…CMA is distinct from macroautophagy as CMA degradation pathway will accurately degrade certain proteins without engulf process and most of its degradation target proteins would be cytoplasm soluble proteins. This selective degradation pathway also contributes to maintenance of cellular homeostasis particularly under stress conditions together with other types of autophagy [44][45][46][47]. In the process of CMA mediated degradation, targeted protein will first be recognized and bind by a cytosolic chaperone, heat shock cognate protein of 70KD (hsc 70).…”
Section: Autophagy Malfunction In Admentioning
confidence: 99%
“…First of all, autophagy is believed to be another major Aβ clearance pathway besides those well-known Aβ degradation enzymes [56]. Autophagy facilitates the degradation and clearance of APP [57] as well as all APP cleavage products including Aβ [47,58], and APP-CTFs (amyloid precursor protein cleaved C-terminal fragment) [59]. In microglia, Aβ has also been found to be degraded by autophagy through the autophagy receptor optineurin [60].…”
Section: Autophagy Dysfunction and Ad-related Pathologymentioning
confidence: 99%